2019
DOI: 10.1111/1475-679x.12268
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Information Processing Costs on Firm Disclosure Choice: Evidence from the XBRL Mandate

Abstract: This paper examines the effect of market participants' information processing costs on firms' disclosure choice. Using the recent eXtensible Business Reporting Language (XBRL) regulation, I find that firms increase their quantitative footnote disclosures upon implementation of XBRL detailed tagging requirements designed to reduce information users' processing costs. These results hold in a difference-in-difference design using matched nonadopting * Foster School of Business, University of Washington.Accepted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(71 citation statements)
references
References 75 publications
3
65
0
3
Order By: Relevance
“…Dong et al (2016) argue that the XBRL mandate reduces stock price synchronicity. Blankespoor (2014) finds that the XBRL mandate prompts firms to increase their footnote disclosures. As well, studies suggest that XBRL adoption reduces information asymmetry (Yoon et al 2011;Li et al 2013), provides incremental information content (Efendi et al 2016), increases information efficiency (Kim et al 2012), increases small institutions' responsiveness to 10-K information (Bhattacharya et al 2018), and constrains opportunistic earnings management (Kim et al 2013).…”
Section: Xbrl Background and Related Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Dong et al (2016) argue that the XBRL mandate reduces stock price synchronicity. Blankespoor (2014) finds that the XBRL mandate prompts firms to increase their footnote disclosures. As well, studies suggest that XBRL adoption reduces information asymmetry (Yoon et al 2011;Li et al 2013), provides incremental information content (Efendi et al 2016), increases information efficiency (Kim et al 2012), increases small institutions' responsiveness to 10-K information (Bhattacharya et al 2018), and constrains opportunistic earnings management (Kim et al 2013).…”
Section: Xbrl Background and Related Studiesmentioning
confidence: 99%
“…On the other hand, firms weigh the costs and benefits of disclosure (Diamond and Verrecchia 1991). Because XBRL facilitates investor use of firm-specific information, thus increasing the benefits of disclosure, firms increase their quantitative disclosures upon implementation of XBRL (Blankespoor 2014). As a consequence, the investor-perceived level of information uncertainty (information risk) decreases and more investors are subsequently attracted to XBRL firms, compared with non-XBRL firms.…”
Section: Impact Of Xbrl Adoption On Breadth Of Ownershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Why do retail investors ignore accounting information? Blankespoor et al (2019) concluded that the cost of monitoring and acquiring accounting information demotivates retail investors using accounting disclosures in stock trading decisions. Although the cost of acquisition and processing of accounting information could avert traders using available accounting disclosures (Bhattacharya, 2001), sometimes they are reluctant to utilize all available information (Malmendier and Shanthikumar, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Integration costs are relevant in papers including Miller [], Lawrence [], Maines and McDaniel [], Chapman et al. [], Drake, Thornock, and Twedt [], and Blankespoor [].…”
mentioning
confidence: 99%